Analysis of the Applicability of Photogrammetry in Building Façade - Siewczyńska, Monika; Zioło, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article evaluates the accuracy of 3D models made from point clouds obtained from photogrammetry. Photographs were taken from ground level and using a drone, and data processing was performed in 3DF Zephyr. The models were compared with the actual dimensions of the buildings. Four different building objects with varying degrees of complexity were analysed.
Keywords: photogrammetry; building facades; 3D model; point cloud; inventory; fotogrametria; fasada budynku; model 3D